Four-Year Teriparatide Followed by Denosumab vs. Continuous Denosumab in Glucocorticoid-Induced Osteoporosis Patients With Prior Bisphosphonate Treatment - Hirooka, Yasuaki; Nozaki, Yuji; Okuda, Saki; Sugiyama, Masafumi; Kinoshita, Koji; Funauchi, Masanori; Matsumura, Itaru (Frontiers in Endocrinology, 2021)
Objectives: In our previous 24-month study, we observed that teriparatide had some advantages over denosumab for bone mineral density (BMD) in glucocorticoid-induced osteoporosis (GIO) patients with prior bisphosphonate treatment. We conducted this extension study to investigate whether the advantage of teriparatide obtained in the first 2 years would be maintained after the switch to denosumab. Materials and Methods: We switched patients who had completed 24-month daily teriparatide treatment to denosumab (switch group, n=18) and compared their BMD every 6 months up to 48 months with the group who continued to receive denosumab (denosumab group, n=16). Results: At 48 months, the lumbar spine BMD increased significantly from baseline in both groups (denosumab: 10.4±8.7%, p<0.001; switch: 14.2±6.8%, p<0.001). A significant increase in femoral neck BMD from baseline occurred only in the switch group (11.2±14.6%, p<0.05); denosumab (4.1±10.8%). The total hip BMD increased significantly from baseline in both groups (denosumab: 4.60±7.4%, p<0.05; switch: 7.2±6.9%, p<0.01). Femoral neck BMD was significantly increased in the switch vs. the denosumab group (p<0.05). Conclusion: In GIO patients with prior bisphosphonate treatment, the advantage of teriparatide may be maintained after the treatment period. A continuous increase in BMD can be expected with teriparatide followed by denosumab.